Applications of Chitosan in Prevention and Treatment Strategies of Infectious Diseases - Genada Sinani; Melike Sessevmez; Sevda Şenel (MDPI AG, 2024)
Chitosan is the most commonly investigated functional cationic biopolymer in a wide range of medical applications due to its promising properties such as biocompatibility, biodegradability, and bioadhesivity, as well as its numerous bioactive properties. Within the last three decades, chitosan and its derivatives have been investigated as biomaterials for drug and vaccine delivery systems, besides for their bioactive properties. Due to the functional groups in its structure, it is possible to tailor the delivery systems with desired properties. There has been a great interest in the application of chitosan-based systems also for the prevention and treatment of infectious diseases, specifically due to their antimicrobial, antiviral, and immunostimulatory effects. In this review, recent applications of chitosan in the prevention and treatment of infectious diseases are reviewed, and possibilities and limitations with regards to technical and regulatory aspects are discussed. Finally, the future perspectives on utilization of chitosan as a biomaterial are discussed.